2021
DOI: 10.3389/fphar.2021.643172
|View full text |Cite
|
Sign up to set email alerts
|

Locus Coeruleus to Paraventricular Thalamus Projections Facilitate Emergence From Isoflurane Anesthesia in Mice

Abstract: Locus coeruleus (LC) sends widespread outputs to many brain regions to modulate diverse functions, including sleep/wake states, attention, and the general anesthetic state. The paraventricular thalamus (PVT) is a critical thalamic area for arousal and receives dense tyrosine-hydroxylase (TH) inputs from the LC. Although anesthesia and sleep may share a common pathway, it is important to understand the processes underlying emergence from anesthesia. In this study, we hypothesize that LC TH neurons and the TH:LC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Similar to volatile anesthetics, the LC-NA system has been tested to regulate general anesthesia induced by propofol and etomidate [ 98 ]. Although LC noradrenergic projections to the midline thalamus exerted similar emergence-promoting effects [ 103 , 104 ], the intracerebral injection of NA or the activation of noradrenergic terminals in the TRN delayed recovery from the propofol anesthesia [ 105 ], indicating diverse effects mediated by different neural circuits.…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…Similar to volatile anesthetics, the LC-NA system has been tested to regulate general anesthesia induced by propofol and etomidate [ 98 ]. Although LC noradrenergic projections to the midline thalamus exerted similar emergence-promoting effects [ 103 , 104 ], the intracerebral injection of NA or the activation of noradrenergic terminals in the TRN delayed recovery from the propofol anesthesia [ 105 ], indicating diverse effects mediated by different neural circuits.…”
Section: Locus Coeruleusmentioning
confidence: 99%
“…LC is the primary source of norepinephrine in the brain and sends abundant outputs to many subregions of the forebrain, making it a vital arousal node [ 73 ]. Chemogenetic activation of LC in rats induces cortical arousal and a noticeable decrease in time to emergence from isoflurane, but the induction time remains unchanged [ 4 , 74 ]. Furthermore, the paraventricular thalamus (PVT) is a wakefulness-promoting region that receives numerous projections from the LC [ 75 ].…”
Section: Chemogeneticsmentioning
confidence: 99%
“…Furthermore, the paraventricular thalamus (PVT) is a wakefulness-promoting region that receives numerous projections from the LC [ 75 ]. Researchers found that chemogenetic inhibition of LC-PVT projections significantly delayed emergence time from isoflurane anesthesia but had no impact on the induction phase [ 74 ]. Thus, although both dopaminergic and noradrenergic neurons belong to the class of monoaminergic neurons, there is a difference between these neurons in the process of consciousness transformation during general anesthesia.…”
Section: Chemogeneticsmentioning
confidence: 99%
“…In Anxiety and Depression, brain transmitters could be modulated by intestinal microbiota (Huang and Wu). The locus coeruleus (LC) tyrosine-hydroxylase (TH) neurons and the TH:LCparaventricular thalamus circuit may be involved in regulating emergence from anesthesia (Ao et al, 2021).Moroz leads us to explore, in an elegant dissertation, the evolutionary aspects of neurons origin. He presents the most relevant hypotheses on the aspects that have given rise to neuronal types, their organization, way of communication, and the mechanisms underlying these characteristics (Moroz).…”
mentioning
confidence: 99%
“…In Anxiety and Depression, brain transmitters could be modulated by intestinal microbiota ( Huang and Wu ). The locus coeruleus (LC) tyrosine-hydroxylase (TH) neurons and the TH:LC-paraventricular thalamus circuit may be involved in regulating emergence from anesthesia ( Ao et al, 2021 ).…”
mentioning
confidence: 99%